A linguistic analysis of slang usage among senior high school students in Midsayap, Cotabato, Philippines - Catig, Rachel Tagle; Parcon, Marissa Navarro (Pascasarjana Universitas Negeri Makassar, 2025)
This study employed a descriptive qualitative approach within a sociolinguistic framework to analyze the use of slang among students. The study focused on thirty-six (36) Grade 12 HUMSS students at a private school in Midsayap, Cotabato, Philippines, and aimed to identify the slang expressions they used, as well as to examine their linguistic features in terms of morphology, syntax, and semantics. The primary data source consisted of dialogue scripts written by the respondents. Findings revealed that the students used seventy-two (72) slang expressions, categorized as sixty-four (64) words, three (3) phrases, and five (5) acronyms. In terms of morphology, slang was formed using free lexical morphemes as well as inflectional and derivational bound morphemes. Regarding syntax, slang followed common sentence structures, including simple, compound, and complex sentences, with identifiable main subjects and main verbs. The most frequently observed sentence patterns were S-V-DO (Subject-Verb-Direct Object) and S-LV-C (Subject-Linking Verb-Complement), with imperative sentences, expressions, and acronyms also being commonly used. In terms of semantics, slang expressions carry both denotative (literal) and connotative (figurative) meanings, reflecting their contextual adaptability and social significance. In conclusion, the findings indicate that slang is an integral part of students' daily interactions. The study confirms that slang is systematically formed through free and bound morphemes and adheres to syntactic structures, demonstrating that it is not merely informal speech but follows linguistic patterns that contribute to meaning-making in communication.